2020
DOI: 10.3390/cells9020441
|View full text |Cite
|
Sign up to set email alerts
|

Role of Insulin-Like Growth Factor Receptor 2 across Muscle Homeostasis: Implications for Treating Muscular Dystrophy

Abstract: The insulin-like growth factor 2 receptor (IGF2R) plays a major role in binding and regulating the circulating and tissue levels of the mitogenic peptide insulin-like growth factor 2 (IGF2). IGF2/IGF2R interaction influences cell growth, survival, and migration in normal tissue development, and the deregulation of IGF2R expression has been associated with growth-related disease and cancer. IGF2R overexpression has been implicated in heart and muscle disease progression. Recent research findings suggest novel a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 88 publications
0
20
0
Order By: Relevance
“…While IGF2R lacks intrinsic kinase activity and acts as a scavenger of extracellular IGF2 [ 13 ], the IRR has been long viewed as an orphan receptor but recent data have demonstrated that the IRR acts as an extracellular Alkali Sensor [ 2 , 14 ].…”
Section: The Igf System: Receptors Ligands and Binding Proteinsmentioning
confidence: 99%
“…While IGF2R lacks intrinsic kinase activity and acts as a scavenger of extracellular IGF2 [ 13 ], the IRR has been long viewed as an orphan receptor but recent data have demonstrated that the IRR acts as an extracellular Alkali Sensor [ 2 , 14 ].…”
Section: The Igf System: Receptors Ligands and Binding Proteinsmentioning
confidence: 99%
“…A previous study showed that Igf-2 up-regulates its own gene expression via the Akt/PKB pathway (35). Elevation of Igf-2 mRNA was found in C2 myoblasts after 24 hours' culture in differentiation medium containing 2-10% horse serum (36), while Erbay et al (2003) suggested that mTOR regulates Igf-2 production at the transcriptional level when cultured under low mitogen conditions (37,38). There has also been a study suggesting that myoblasts under low mitogen conditions have elevated levels of IGFBP5, which helps concentrate IGF-2 to a threshold level which triggers the IGF-1R pathway leading to differentiation (39,40).…”
Section: Dystrophin-de Cient Myoblasts Do Not Achieve Terminal Differmentioning
confidence: 99%
“…The other two receptors of the family are the IGF2R and IRR. The IGF2R is a type-1 transmembrane glycoprotein which lacks intrinsic kinase activity and acts by scavenging extracellular IGF2, thus titrating IGF2 levels and suppressing IGF signaling [22]. On the other hand, little is known about the IRR, despite the close homology with the IGF1R and IR.…”
Section: The Igf System: Major Components and Signal Transductionmentioning
confidence: 99%